2012
DOI: 10.1161/circep.112.971341
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Ventricular Tachycardia in Nonischemic Heart Disease

Abstract: Background-Catheter ablation of ventricular tachycardia (VT) in nonischemic heart diseases can be challenging, and outcomes across different diseases are incompletely defined. The aim of this study was to describe the outcomes after catheter ablation for nonischemic VT in a large cohort and to compare the electrophysiological findings and outcomes according to the type of underlying disease. Methods and Results-Of the 891 consecutive patients undergoing catheter ablation for ventricular arrhythmias, 226 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 41 publications
4
70
2
Order By: Relevance
“…In one retrospective study on 226 NICM patients undergoing ablation for drug‐refractory VT, the survival was achieved, with no further requirement for heart transplants and readmissions for VT recurrences, in 173 (77%) patients. In that study, the patients with ARVC had better outcomes than those with DCM, whereas the patients with sarcoidosis had the worst outcomes 48, 77. Another recent retrospective study on 282 NICM VT patients yielded consistent results in achieving a long‐term freedom from VT in 69% of cases 78.…”
Section: Management Of Vt In Nicmmentioning
confidence: 81%
“…In one retrospective study on 226 NICM patients undergoing ablation for drug‐refractory VT, the survival was achieved, with no further requirement for heart transplants and readmissions for VT recurrences, in 173 (77%) patients. In that study, the patients with ARVC had better outcomes than those with DCM, whereas the patients with sarcoidosis had the worst outcomes 48, 77. Another recent retrospective study on 282 NICM VT patients yielded consistent results in achieving a long‐term freedom from VT in 69% of cases 78.…”
Section: Management Of Vt In Nicmmentioning
confidence: 81%
“…In a recent study in patients with NIDCM VT, noninducibility failed to predict long-term success even after epicardial ablation. 12 The Heart Center of Leipzig VT (HELP-VT) study was conducted prospectively to compare the outcomes after radiofrequency catheter ablation of VT in NIDCM and ICM. Furthermore, we sought to determine the predictors for the short-and long-term success rates in NIDCM.…”
Section: Clinical Perspective On P 736mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Studies addressing the outcomes in nonischemic dilated cardiomyopathy (NIDCM) patients are fewer, include smaller groups of patients, and have reported worse outcomes. [8][9][10][11][12] A more recent multicenter trial in epicardial VT ablation suggested comparable outcomes in ischemic cardiomyopathy (ICM) and NIDCM, with a reported VT recurrence in 39.3% in NIDCM versus 34.7% in ICM. 13 …”
mentioning
confidence: 99%
“…This difference in the underlying diseases might lead to different ablation outcomes. Tokuda et al [39] recently reported the long-term follow-up outcomes of VT ablation in patients with non-IHD. In that study, the ARVC-VT ablation outcomes were significantly better than the NIDCM-VT ablation outcomes, which is consistent with our study results.…”
Section: Non-ischemic Dilated Cardiomyopathymentioning
confidence: 99%